E-Food Commerce, Nutrition Economics and Consumer Behaviour: Before And After Covid-19 - Hamadeh, Sima (British Journal of Marketing Studies, 2021)
Consumer behaviors and purchases are complex concepts and strongly influenced by personal, psychological, sociocultural and environmental factors. This paper proposed an innovative comprehensive consumer behavior framework for use as a logical tool that assists in planning for local and national food programs aimed at complex socioeconomic, environmental and public health problems such as COVID-19. The progress of the Internet of things and the social media reported here provides a platform for accelerated actions that could have major positive implications for public health nutrition in the post COVID-19 world.